Mastery of Student Concepts in Physics Learning: Analysis of student learning outcomes based on teacher treatment after using the Discovery Learning Model - Boby Syefrinando; Ayu Sofna; Cici Pramita; Tasa Ratna Puri; Al Fajri Adha; Tegolasdi Irmansyah; Fuzan Sulman (Universitas Muhammadiyah Enrekang, 2023)
This research aims to determine the effect of the discovery learning model on mastery of the concept of temperature and heat material. This research uses a quantitative type of research with a quasi-experimental design using Posttest Only Control Group Design. The population of this research is class X for the 2023/2024 academic year at SMK Negeri 09 Muaro Jambi. Sampling used a purposive sampling technique to obtain 2 classes, namely the experimental class with 18 students and the control class with 18 students. Both classes were given test questions in the form of a multiple choice posttest consisting of 5 questions. Based on tests and data analysis, the average score for the experimental class was 70.00 with a standard deviation of 19.70 and the average score for the control class was 58.00 with a standard deviation of 24.22. From the results above, it is found that mastery of concepts using the discovery learning model is better than mastery of concepts without using a learning model. It can be concluded that the discovery learning model influences students' mastery of concepts in temperature and heat material. This is because learning using the discovery learning model can increase students' activeness in learning, especially temperature and heat material.